PENERAPAN HUKUM QISHASH UNTUK MENEGAKKAN KEADILAN - Anisah, Siti (Journal of Islamic Law Studies, 2018)
The rise of crimes that occurred in Indonesia has made anxiety among the society. Regulation in Indonesian law has not been able to make the perpetrators deterrent, causes murders continue to occur within this decade. Although the perpetrators have been on trial by a court of law Indonesia, they has not yet received punishment commensurate with what they have done. Therefore Indonesia require a law to prosecute the perpetrators of the fairest, which is Qishash law. Qishash is an Islamic law that provides for punishment commensurate with the term “soul be paid with their lives”. This Qishash law should be applied in the face of the earth, but in modern times not a few people who do Qishash rejection of the law on behalf of human rights, although many lessons learned when Qisas law is applicable.